Financial Development and Inequality in the Global Economy - Maximilian von Ehrlich; Tobias Seidel (Center for Economic Studies and ifo Institute (CESifo), 2016)
We build a heterogeneous-firms model with firm-specific wages and credit frictions to study the role of financial development for inequality in the global economy. If there are many small firms, better access to external funds reduces wage inequality and unemployment. In contrast, if there are many highproductive firms (those that export), financial development may have opposite effects - especially if trade costs are low. In sum, the implications of financial development for inequality depend on the size distribution of firms and on the costs of exporting. Trade liberalization, however, raises inequality unambiguously.
Keywords: F16; F65; 330; financial development; credit constraints; international trade; inequality